POLITICAL MOVEMENT WE ARE: FROM THE EMERGENCE TO THE FRACTIONATION OF THE LGBTQIA+ STRUGGLE - Barros, Édna Maria Rodrigues Moura; Pereira, Guilherme do Nascimento; Ataliba, Patrick Muniz; Araujo, Romildo de Castro; de Souza, Solange Maria Batista (Seven Editora, 2024)
The present work aims to understand the emergence and consolidation of the LGBTQIA+ political movement in Brazil, focusing on the 1970s and 1980s. The work was guided by the questioning of how and why the LGBTQIA+ political movement originated in Brazil? The investigation was based on a bibliographic and documentary research, anchored in the materialist-dialectical method. The theoretical support was given with the works of Cruz (2018), Green (2018), Mott (2018), Quinallha (2022), Trevisan (2018) among other authors dedicated to the theoretical unveiling of the problem. The historical moment that gave rise to the movement, the importance of the process of mass communication through the press, the political-ideological internal struggles for the conception of the LGBTQIA+ social and political movement and the reconfiguration of the homosexual movement in Brazil in the 1990s are highlighted. In the phase of the conclusions, the period is identified as fundamental for the organization of the initial struggles against homophobia and for the affirmation of the movement as instruments of collective struggles for rights. DOI:https://doi.org/10.56238/sevened2024.031-020